Development of a performance analysis model for small and medium enterprises in Iran - Sorooshian, Shahryar (2012)
Various factors were observed to affect small and medium enterprises’performances for their success and failure in business. The main objectives of this study are to identify the critical factors affecting small and medium enterprises (SMEs) performance and modeling the factors. Previous research on the business success or failure did not provide detailed explanation to SME performances. Particularly, few research has focused on the factors affecting the performance of established SMEs; even though from business environment the need for SME performance analysis system is alarming. Empirical data of this study, were based on extensive survey and interviews. The survey comprised of 20 experts and 321 independent operators in the manufacturing sectors of small and medium industries of entrepreneurs in Iran. Qualitative and quantitative analysis methods were used for data analysis. Specifically interview and structural equation modeling were the main methods of this study. From the findings, a multi-criteria model was built for generic theory of business success in the SME-context. The model consists of two main constructs: Strategy formulation activities (SFA) and strategy administration activities (SAA). There are five latent sub-dimensions which are internal and external environment scanning, strategy formulation, strategy implementation and strategy control. This research found a significant relationship between SFA and SME Performance. Also, from the result reports a significant relationship between SAA and SME performance. The relationship between SFA and SAA was also reported to be significant. The result strongly suggests that entrepreneurs of SMEs should take necessary actions in aligning their strategy administration activities with the requirements of strategy formulation activities. This study improves the existing theories in that it not only establishes a relationship between strategy formulation activities and strategy administration activities, but also it calculates how this relationship impacts the SME performance, using structural equation modeling method. The model provides a structural systematic method for analysis of business strategic management and its impact on performance of the company both in subjective (qualitative) and the objective (quantitative) terms. The main ability of the model is it can analyze SME performance based on observed and latent variables of strategic management using structural equation model and path coefficients. Another ability of the model is it can be used to benchmark, as it can measure the current performance by the use of two generic latent sub-dimensions of performance,which include financial and non-financial (operational and constituency) performance. This study worked with total number of 56 variables (observed or latent), which direct and indirect relationship between these variables and performance of SMEs were systematically analyzed. Series of tests supported validity, accuracy and feasibility of the model, and it was found that nascent and acting entrepreneurs, organizations fostering SME development, financiers, public policy makers, SME advisors, and other stakeholders of SMEs would benefit the most from the model.